REALISM AS A REFLECTION OF INDUSTRIAL SOCIETY IN CHARLES DICKENS’S HARD TIMES - Mamatova Shahribonu Badriddin qizi (Ta’lim innovatsiyasi va integratsiyasi, 2025)
Abstract This paper examines the manifestation of literary realism in Charles Dickens’s Hard Times (1854) and its function as a reflection of the industrial society of nineteenth-century England. Dickens’s portrayal of Coketown and its inhabitants provides a realistic depiction of the social, moral, and psychological consequences of industrialization. Using textual and contextual analysis, this study explores how realism serves not merely as a descriptive technique but as a powerful instrument of social criticism. The findings suggest that Dickens’s realism exposes the moral decay and emotional sterility of industrial capitalism while advocating for compassion, imagination, and moral integrity.